PENGARUH pH DAN WAKTU FERMENTASI UNTUK MENGHASILKAN ENZIM AMILOGLUKOSIDASE DARI Aspergillus niger - Fatmawati Nur (Teknosains, 2019)
This study is aimed to know the ability of Aspergillus niger in producing amyloglucosidase enzyme through fermentation technology by exploiting marquisa waste's peel and coated seed under the condition of variation pH and fermentation time. Design used is Randomized Complete Block along with the respective variation of pH is pH 4.0, 4.5, 5.0, and 5.5, through fermentation time is 3, 4, 5 , and 6 x 24 hours, duplo, which is analyzed with F test, then tested with Least  Significant Difference (LSD). The result of study shows the highest glucose concentration representing job of amyloglucosidase enzyme at coated seed substract is fermentation time 5 x 24 hours pH 4.5 which amounts 51.964 µg/ml.